Answer: ![Vertex: y=\dfrac{1}{2}(x-2)^2-7](https://tex.z-dn.net/?f=Vertex%3A%20y%3D%5Cdfrac%7B1%7D%7B2%7D%28x-2%29%5E2-7)
![Standard: y=\dfrac{1}{2}x^2-2x-5](https://tex.z-dn.net/?f=Standard%3A%20y%3D%5Cdfrac%7B1%7D%7B2%7Dx%5E2-2x-5)
Transformations: vertical shrink by a factor of 1/2,
horizontal shift 2 units to the right,
vertical shift 7 units down.
<u>Step-by-step explanation:</u>
Vertex form: y = a(x - h)² + k
Standard form: y = ax² + bx + c
Given: Vertex (h, k) = (2, -7), the y-intercept (0, c) = (0, -5)
Input those values into the Vertex form to solve for the a-value
-5=a(0 - 2)² - 7
2 = a(- 2)²
2 = 4a
![\dfrac{1}{2}=a](https://tex.z-dn.net/?f=%5Cdfrac%7B1%7D%7B2%7D%3Da)
a) Input a = 1/2 and (h, k) = (2, -7) into the Vertex form
![\large\boxed{y=\dfrac{1}{2}(x-2)^2-7}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7By%3D%5Cdfrac%7B1%7D%7B2%7D%28x-2%29%5E2-7%7D)
b) You can plug in a = 1/2, c = -5, (x, y) = (2, -7) to solve for "b"
or
You can expand the Vertex form (which is what I am going to do):
![y=\dfrac{1}{2}(x-2)^2-7\\\\\\y=\dfrac{1}{2}(x^2-4x+4)-7\\\\\\y=\dfrac{1}{2}x^2-2x+2-7\\\\\\\large\boxed{y=\dfrac{1}{2}x^2-2x-5}](https://tex.z-dn.net/?f=y%3D%5Cdfrac%7B1%7D%7B2%7D%28x-2%29%5E2-7%5C%5C%5C%5C%5C%5Cy%3D%5Cdfrac%7B1%7D%7B2%7D%28x%5E2-4x%2B4%29-7%5C%5C%5C%5C%5C%5Cy%3D%5Cdfrac%7B1%7D%7B2%7Dx%5E2-2x%2B2-7%5C%5C%5C%5C%5C%5C%5Clarge%5Cboxed%7By%3D%5Cdfrac%7B1%7D%7B2%7Dx%5E2-2x-5%7D)
c) Use the Vertex form to describe the transformations as follows:
- a is the vertical stretch (if |a| > 1) or shrink (if |a| < 1)
- h is the horizontal shift (positive is to the right, negative is to the left)
- k is the vertical shift (positive is up, negative is down)
![y=\dfrac{1}{2}(x-2)^2-7](https://tex.z-dn.net/?f=y%3D%5Cdfrac%7B1%7D%7B2%7D%28x-2%29%5E2-7)
a = 1/2 --> vertical shrink by a factor of 1/2
h = 2 --> horizontal shift 2 units to the right
k = -7 --> vertical shift 7 units down